Current Evidence Regarding Routine Antibiotic Prophylaxis in Hand Surgery. (May 2018) - Dunn, John C.; Fares, Austin B.; Kusnezov, Nicholas; Pirela-Cruz, Miguel; Gonzalez, Gilberto; Orr, Justin D.; Pallis, Mark
Background: Although routine antibiotic prophylaxis immediately preceding an orthopedic surgery has become the standard of care in most cases, this practice is poorly defined in hand surgery. The purpose of this analysis is to review the most current literature of antibiotic use in hand surgery.Methods: A careful review of the literature regarding routine antibiotic prophylaxis in hand surgery was made. Current relevant resources were used in the construction of this review.Results: There is a mixed consensus on the role for prophylactic antibiotics in hand surgery with some resources and data showing support and others opposed.Conclusions: Based on the current literature, the authors recommend the following patient characteristics not receive antibiotics: clean hygienic patients, without autoimmune disease, and those not taking steroid medication. Surgical characteristics that would render prophylaxis unnecessary include those without hardware, those without reasonable risk of hematoma formation, or those performed at an ambulatory surgery center as opposed to a large hospital. However, the decision should be made on a case-by-case basis weighing the evidence presented.